2020
DOI: 10.3389/fphar.2020.00563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficiency of Vasopressin or Its Analogs in Comparison With Catecholamines Alone on Patients With Septic Shock: A Systematic Review and Meta-Analysis

Abstract: Background: Vasopressin is an efficient remedy for septic shock patients as its great capacity in promoting hemodynamic stabilization. The aim of current systematic review and meta-analysis is to compare the clinical efficiency of vasopressin or its analogs with sole catecholamines on patients with septic shock.Methods: A systematic search of Cochrane Library, EMBASE, and PubMed online databases was performed up to 30 Oct 2019 to identify randomized controlled trials comparing use of vasopressin or its analogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Yao et al. 26 found no association between vasopressin use and overall incidence of adverse events or arrhythmias. Higher incidence of digital ischemia was shown in their meta-analysis which may be reflective of patients in those studies having shock, concomitant catecholamine use, or vasopressin.…”
Section: Discussionmentioning
confidence: 97%
“…Yao et al. 26 found no association between vasopressin use and overall incidence of adverse events or arrhythmias. Higher incidence of digital ischemia was shown in their meta-analysis which may be reflective of patients in those studies having shock, concomitant catecholamine use, or vasopressin.…”
Section: Discussionmentioning
confidence: 97%
“…As the adverse effects of vasopressin, ischemia events, such as digital ischemia ( 6 , 7 ), mesenteric ischemia ( 8 , 9 ), myocardial ischemia, and alterations in circulation dynamics ( 10 ) may be induced by strong vasoconstriction. However, recent clinical studies suggested that these adverse events are less frequent than previously reported, except for digital ischemia, when the appropriate dosage is administered ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 83%
“…High-dose vasopressin may induce digital ( 6 , 7 ), mesenteric ( 8 , 9 ), and myocardial ischemia ( 10 ). Previous case series and clinical trials suggested that the administration of more than 0.05 U/min increased the risk of these adverse effects ( 11 ), and, thus, <0.03 U/min is recommended ( 5 ). However, few studies have investigated the effects of a vasopressin bolus.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews with meta-analyses evaluating Vasopressin and its analogs compared to solely using catecholamines found con icting data on the reduction of 28 days mortality (22,45). Nonetheless, there was a pronounced trend for increased risk of digital ischemia in the vasopressin or analogs group.…”
Section: Discussionmentioning
confidence: 99%